Interpreting “Urgent Reasons” in Marriage Dispensation Cases: A Socio-Legal Study at the Pangkalan Bun Religious Court - Jumrotunisak; Desi Erawati; Masdar Hilmy (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
The phrase “urgent reasons” in Indonesian marriage dispensation law is normatively open yet operationally undefined, creating interpretive space that contributes to disparities in judicial decisions. While prior studies explain these disparities through regulatory weakness or judicial discretion, they rarely examine how such normative ambiguity is socially reproduced through judicial practice. Addressing this gap, this study analyses how judges construct the meaning of “urgent reasons” in pregnancy-related marriage dispensation cases and how this process reflects the interaction between legal structure and local social norms. Using a socio-legal approach, the research examines 43 decisions (2020-2025) from the Pangkalan Bun Religious Court and in-depth interviews with three judges.Drawing on Anthony Giddens’ Structuration Theory, the study argues that normative ambiguity does not merely generate discretion but operates as a structuration mechanism through which judges reproduce and negotiate legal meaning inconcrete cases. The findings reveal three dominant interpretive patterns: (1) urgency as moral restoration and protection of family honour, (2) urgency as safeguarding the best interests of the child, and (3) urgency as maintaining religious and social stability. These patterns demonstrate that judicial disparities stem not from inconsistency but from the activation of different normative orientations when judges confront ambiguous legal structures within a specific socio-cultural context.Theoretically, this study contributes to socio-legal scholarship by showing how vague legal norms function as institutional media for the reproduction of legal pluralism through judicial agency. Practically, the findings highlight the need for clearer operational guidelinessuch as minimum age thresholds, psychological assessment standards, and child protection recommendations, to balance legal certainty, judicial discretion, and child rights protection in marriage dispensation policy.